40 Sentinel lymph node mapping alone compared to more extensive lymphadenectomy in patients with uterine serous carcinoma. (18th September 2019) - Basaran, D; Bruce, S; Aviki, E; Mueller, J; Broach, V; Cadoo, K; Soslow, R; Alektiar, K; Abu-Rustum, N; Leitao, M
Abstract : Objectives: To assess survival among patients with uterine serous carcinoma (USC) who underwent sentinel lymph node (SLN) mapping alone, compared with patients who underwent systematic lymphadenectomy (LND). Methods: Newly diagnosed USC at our institution between 1/1/1996 and 12/31/2017 were reviewed. Patients were assigned to two cohorts: those who underwent SLN mapping alone (SLN Cohort); and those who underwent systematic [pelvic and paraaortic] LND without SLN mapping (LND Cohort). Progression-free survival (PFS) and overall survival (OS) were estimated using the Kaplan-Meier method. Results: In total, 245 patients were available for analysis. Of these, 79 (32.2%) underwent only SLN mapping and 166 (67.7%) underwent systematic LND. Patients in the SLN cohort had a median age of 66 years, compared to 68 years in the LND cohort (p>0.05). Median follow-up time was 23 months (range, 1–96) in the SLN cohort and 66 months (range, 4–265) in the LND cohort (p<0.001). In patients with stage I/II disease (n=160, 60.1%), the 2-year OS was 96.6% (SE ±3.4) in the SLN cohort and 89.6% (SE ±2.2) in the LND cohort (p=0.8). In patients with stage III disease (n=77), the 2-year OS was 73.6% (SE ±10.2) in the SLN cohort and 77.3% (SE±5.8) in the LND cohort (p=0.8). Conclusions: SLN mapping alone and systematic pelvic and paraaortic nodal dissection (LND) led to similar survival outcomes in patients with stage I-III USC. In our practice, the SLN mapping algorithm has replaced systematic LND as the primary staging modality in the setting of apparent uterine-confined endometrial serous cancer.